Radicle protrusion and methods for overcoming the wheat seed dormancy (Revista de Ciências Agroveterinárias, 2016)
The objective was to study the effectiveness of treatments to overcome dormancy of Triticum aestivum L. seeds used four seed lots (1, 2, 3 and 4), BRS Guamirim with an initial moisture content of 12.5%. The treatments were: pre-cooling temperature of 5 to 10 °C; pre-drying temperature of 30 to35 °C; pre-drying at 50 °C for a period of undergoing exposure 72 and 96 h; imbibition of the germination test substrate using solution of gibberellic acid and potassium nitrate and untreated seeds (control). Time of radicle protrusion was assessed by soaking curve. The experimental design was completely randomized in a 4 x 6 factorial (seed lots x treatments to overcome dormancy), with five repetitions. In conclusion, lots 2 and 4 had similar performance in the imbibition curve, having a water content of 43.2 and 40.7%, respectively, after a 16 h period due to the higher degree of dormancy of lots with 30 and 38% germination; method using the thermal temperature of 30 to 35 and 50 °C (72 h) has increased efficiency in overcoming wheat seed dormancy being performed in less time when compared with test currently recommended precooling.
Keywords: Triticum aestivum L.; germination; viability; imbibitions curve.